Association of Malnutrition in Patients Admitted with Complete Heart Block: A Nationwide Analysis - Nahush Bansal; Sonaal Singla; Jasneet Kaur; Nikita Sharma; Feehaan Sultan; Shuhao Qiu (Obesities)
Background: Complete heart block (CHB) is a cardiac conduction disorder that can be fatal if not treated promptly. Malnutrition has been shown to have a significant impact on various cardiac conditions. Aim: The objective was to determine if the nutritional status influences the outcomes in patients with CHB. Methods: A retrospective study was conducted using the United States Inpatient Sample database on patients admitted with complete heart block. Outcomes were compared between the patients with and without concomitant malnutrition. Results: The study included 37,480 patients with complete heart block, of whom 603 (1.61%) had malnutrition. Compared to patients without malnutrition, patients with malnutrition had higher adjusted in-hospital mortality rates (aOR 2.61; 95% CI 1.46–3.48), longer length of stay (LOS) (mean increase 2.23 days; p < 0.01), and higher hospital charges (mean increase USD 76,907.32; p < 0.01). The malnourished group also had significantly higher rates of cardiogenic shock (aOR 2.80; 95% CI 1.56–5.03; p < 0.01) and acute respiratory failure (aOR 2.65; 95% CI 1.67–4.22; p < 0.01). Patients with malnutrition had significantly lower rates of permanent pacemaker (aOR 0.57; 95% CI 0.38–0.86; p < 0.01) and longer delay to permanent pacemaker intervention (mean increase 1.38 days; p = 0.014). The impact on outcomes was worse in patients with severe malnutrition compared to those with mild to moderate malnutrition. Conclusions: Malnutrition is associated with significantly worse outcomes in CHB admissions, including higher mortality, resource utilization, complications, and lower and delayed pacemaker intervention. Individualized and timely nutritional interventions might potentially play a key role in improving outcomes in these patients.